2016
DOI: 10.1002/ejic.201600999
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structures of Mono‐ and Dinuclear Molybdenum Complexes with Reduced α‐Diimine Ligands

Abstract: The mononuclear molybdenum complex [Mo( H L) 2 ] (1), Mo-Mo single-bond compound [ H LClMo(μ-Cl) 3 Mo H LCl] [2; Mo-Mo 2.832(7) Å], and Mo≡Mo triple-bond compounds [Mo 2 Cl 2 (μ-H L) 2 ] [3; Mo-Mo 2.194(6) Å] and [Mo 2 Cl 2 (μ-Cl)(μ-H L)Cl 2 Na(THF) 3 ] [4; Mo-Mo 2.167(2) Å] have been synthesized by the reaction of H L { H L = [(2,6-iPr 2 C 6 H 3 )NCH] 2 } with 0.5, 1, and 2 equiv. of MoCl 5 and different amounts of Na metal. In the [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…18 In accordance with the trend, if on one hand coordination adducts of TiCl 4 and ZrCl 4 with αdiimines have been prepared by simple Lewis acid-base combination, 19 on the other hand all the reported reactions of HVM-chlorides, i.e. NbCl 5 , 20 TaCl 5 , 21 MoCl 5 22 and WCl 6 , 23 have been performed in the presence of reductants (e.g. Na/naphthalene, 21b Na, 22 Zn/Hg 23b ) or a chlorine abstractor agent [1-methyl-3,6-bis(trimethylsilyl)-1,4-cyclohexadiene 20,21a,23a ], in order to preliminarily reduce the metal centre.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…18 In accordance with the trend, if on one hand coordination adducts of TiCl 4 and ZrCl 4 with αdiimines have been prepared by simple Lewis acid-base combination, 19 on the other hand all the reported reactions of HVM-chlorides, i.e. NbCl 5 , 20 TaCl 5 , 21 MoCl 5 22 and WCl 6 , 23 have been performed in the presence of reductants (e.g. Na/naphthalene, 21b Na, 22 Zn/Hg 23b ) or a chlorine abstractor agent [1-methyl-3,6-bis(trimethylsilyl)-1,4-cyclohexadiene 20,21a,23a ], in order to preliminarily reduce the metal centre.…”
supporting
confidence: 52%
“…NbCl 5 , 20 TaCl 5 , 21 MoCl 5 22 and WCl 6 , 23 have been performed in the presence of reductants (e.g. Na/naphthalene, 21b Na, 22 Zn/Hg 23b ) or a chlorine abstractor agent [1-methyl-3,6-bis(trimethylsilyl)-1,4-cyclohexadiene 20,21a,23a ], in order to preliminarily reduce the metal centre. This synthetic method permits the clean isolation of coordination compounds containing intact α-diimine ligands, thus quenching the strong activation potential typical of the high valent metal species.…”
mentioning
confidence: 99%
“…7 Besides, the reactivity studies with high valent metal compounds (oxidation state of the metal ≥ 4), that are potential, strong oxidizing agents, are exceedingly rare in the literature. 4,8 With reference to homoleptic, high valent transition metal chlorides, the reactivity of NbCl 5 , 9 TaCl 5 , 10 MoCl 5 11 and WCl 6 12 with α-diimines has aroused a recent and notable consideration. However, all the described reactions have been performed with prior reduction, by one or two electrons, of the metal centre.…”
mentioning
confidence: 99%
“…However, up to now, no analogous dimetallic compounds with a metal−metal bond could be isolated other than for Mg, although theoretical calculations predict that some of these low-valent alkaline metal compounds should be stable. 48,49 In the case of αdiimine ligands, computations also indicated that the [LMML] dimer (M = Be to Ba) can be stabilized by the dianionic dad ligand, 50 but attempts to synthesize the possible dimeric calcium(I) compound yielded the Ca(II) complexes (16)(17)(18)(19)(20) as mentioned above.…”
Section: Complexes Of Groups 1 and 2 Metalsmentioning
confidence: 98%
“…4,5 In a few cases, neutral dad ligands can also bond to low-valent metal centres, such as in Ni(0) complexes with alkenes, L'Ni(C2H4)2 17 and LNi(alkene), 18 which may be facilitated by back bonding to the alkene thereby depleting the electron density at nickel(0). For the monoanionic and dianionic dad ligands, there are several coordination modes, including the normally seen σ 2 -, σ 2 ,π-and μ-(σ 2 )(σ 2 ,π) in which the two N atoms are arranged in a cis (chelating) conformation, and the uncommon bridging modes, either cisμ-σ 1 ,σ 1 - [19][20][21] or trans-μ-σ 1 ,σ 1 -coordination [22][23][24] where the two N atoms adopt a cisor trans orientation, respectively, and each of them coordinates to one metal centre (Scheme 2). These two reduced forms of dad ligands are found to be able to stabilize low-valent metal centres.…”
Section: Various Complexes Of α-Diimine Ligandsmentioning
confidence: 99%